The Challenges of Reopening Universities in the Corona Pandemic From Students’ Perspectives - Seyed Mohammad Hosein Javadi; Mohammad Sabzi Khoshnami; Sara Noruzi; Majid Saffarnia; Seyed Hasan Emami Razavi; Mahboobeh Tavakoli (Health in Emergencies & Disasters Quarterly)
Background: Iran is one of the few countries that closed schools and universities since the beginning of the pandemic. This study examines students’ views on the challenges of reopening universities. Materials and Methods: The study is cross-sectional, and its statistical population consisted of students of Iranian universities. Data were collected by an electronic questionnaire (N=20534) based on a review of resources, interviews with stakeholders, and meetings with experts. Results: Half of the families agreed with reopening the universities, and the other half opposed it. About 56% of the participants rated their family’s economic situation moderate. During the quarantine and university closing, they faced many challenges with their family members, and 76.6% were admitted. The relationship between family agreement with the reopening of the university and sex, vaccination of family members, and history of coronavirus infection by family members is direct and strong. Students with poorer economic status had less passive attendance and less satisfaction. Conclusion: Students and their parents have concerns about the reopening, which, if appropriately addressed, will increase reluctance and motivation.